Charles Trevelyan, John Mitchel and the historiography of the Great Famine - Christophe Gillissen (Revue Française de Civilisation Britannique)
The books of Charles Trevelyan (1847) and John Mitchel (1860) constitute pioneering writings on the Great Famine and despite their extreme views they defined a framework which helps to understand later historiographical developments, from nationalism to revisionism and to post-revisionism. Beyond theoretical considerations as such, another factor of those historiographical trends is the context in which historians have worked: the state of Anglo-Irish relations and the conflict in Northern Ireland have also contributed to shaping interpretations of the Famine.